PENGARUH SUASANA TOKO TERHADAP KEPUASAN PELANGGAN - Pandapotan, Rizky Carlos; Setiawardani, Maya (POLITEKNIK NEGERI BANDUNG, 2016)
Store atmosphere is a condition in a store that is formed by the tangible and intangible components, which can influence consumer behavior, such as customer satisfaction. Customer satisfaction is the level of one's feelings after comparing the performance or perceived value with expectations. This study used a quantitative method, such questionnaires which distributed to 142 respondents and also the observations results. In addition, this study uses three types of analysis to achieving the objectives, namely descriptive analysis, correlation analysis and linear regression analysis. Meanwhile, the results of this study indicate that store atmosphere good categories with a mean value of 3.72 and customer satisfaction at high category with a mean value of 4.09. In addition, the coefficient of determination test indicates that the effect of store atmosphere contributes 27.7%to customer satisfaction and the other of 72.3% is the contribution of the influence from the other variables which not examined in this study. Based on test results obtained linear regression equation such Y = 26.711 + 0,367X. This is show that if there is additional to the store atmosphere, the customer satisfaction will be increased by 0,367. And the results of hypothesis testing indicate that there are significant influences between store atmosphere and customer satisfaction at theToko Buku Togamas Branch Supratman Bandung.